2015
DOI: 10.1007/s12298-015-0289-z
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic stress induces change in Cinnamoyl CoA Reductase (CCR) protein abundance and lignin deposition in developing seedlings of Leucaena leucocephala

Abstract: Aboitic stress such as drought and salinity are class of major threats, which plants undergo through their lifetime. Lignin deposition is one of the responses to such abiotic stresses. The gene encoding Cinnamoyl CoA Reductase (CCR) is a key gene for lignin biosynthesis, which has been shown to be over-expressed under stress conditions. In the present study, developing seedlings of Leucaena leucocephala (Vernacular name: Subabul, White popinac) were treated with 1 % mannitol and 200 mM NaCl to mimic drought an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 33 publications
2
55
0
2
Order By: Relevance
“…Several studies have shown that lignin accumulation and high levels of lignin biosynthetic gene expression are important for abiotic stress tolerance (Hu et al, 2009;Shafi et al, 2015;Srivastava et al, 2015). In this study, heavier deposition of lignin was observed specifically in the secondary xylem and phloem fibers of BpNAC012-OE transgenic plants under salt and osmotic stress conditions, which was consistent with the results that BpNAC012 highly induced the expression of lignin biosynthetic genes in response to abiotic stress treatments.…”
Section: Overexpression Of Bpnac012 Induces Enhanced Lignification Agsupporting
confidence: 91%
“…Several studies have shown that lignin accumulation and high levels of lignin biosynthetic gene expression are important for abiotic stress tolerance (Hu et al, 2009;Shafi et al, 2015;Srivastava et al, 2015). In this study, heavier deposition of lignin was observed specifically in the secondary xylem and phloem fibers of BpNAC012-OE transgenic plants under salt and osmotic stress conditions, which was consistent with the results that BpNAC012 highly induced the expression of lignin biosynthetic genes in response to abiotic stress treatments.…”
Section: Overexpression Of Bpnac012 Induces Enhanced Lignification Agsupporting
confidence: 91%
“…Drought stress had a positive effect on lignin deposition and deepened the lignified degree of developing seedling stems in Leucaena leucocephala [61]. The expression of CAD (cinnamyl alcohol dehydrogenase) and several other genes involving in lignin biosynthesis increased during 48h to 72h under water stress in rice root [62].…”
Section: Discussionmentioning
confidence: 99%
“…[5,41,99,[145][146][147][148][149][150][151] The response of these pathways to abiotic stresses is crucial for understanding the full biological role of lignin in the plant. [5,145] Effects of abiotic stress can be analysed either by individually introducing stresses,e .g., growing the plant in amedium with high salinity), [150,152] or by monitoring how the plants perform in ag reenhouse setting vs.i nf ield trials. [153] Recent review literature provides ac omparison of the impacts of biotic and abiotic stress on plant fitness when transferring from ac ontrolled greenhouse environment to field trials.…”
Section: Practical Challenges Of Lignin Bioengineeringmentioning
confidence: 99%